Keanekaragaman Serangga dan Tingkat Kerusakan Akibat Serangan Hama pada Tanaman Jeruk - Melinda, Aura Tirsa; Dyah Rini Indriyanti; Priyantini Widiyaningrum; Niken Subekti (Universitas Negeri Semarang, 2024)
Citrus are a horticultural commodity that has high economic value and tends to be liked by many people. In the Bawen area, Semarang Regency, there is a plantation that cultivates various types of orange plants. Many citrus plants have signs of pest attacks that have not yet been identified. This research aims to obtain data related to insect diversity and the level of damage caused by insect pest attacks on citrus plants. This research is an exploratory type of research, using a survey method. The research location was determined using purposive sampling by taking three fields of Siam Honey, Sumowono and Pamello oranges. Insect sampling was carried out using pitfall trap, yellow trap, direct observation and interviews. The results of the study showed that the diversity index was H' = 3.3, honey siam = 3.3, pamello orange (H' = 3.1) and sumowono siam (H' = 2.9). The similarity value of the three types of orange is 0.8 and the dominance is 0.05 (honey siamese), 0.06 (pamello) and 0.07 (sumowono). At the time of research, orange plants were in the generative phase so they could attract more insects. The level of damage due to pest attacks is classified as moderate. The conclusion of this research is that the highest species diversity value is Siam Honey, then Pamello orange and Siam Sumowono, the presence of insects is evenly distributed and no one species dominates. The benefit of this research is to obtain information regarding the diversity of insect types and the level of damage caused by insect pest attacks.